Frontiers of optic nerve regeneration research: an analysis of the top 100 most influential articles in the field from 2005 to 2025 - Saijilafu; Chen, Peng; Ye, Lingchen; Shen, Yuxi; Wang, Qi; Chen, Xuanwen; Chimedtseren, Chimedragchaa; Zhang, Junqian; Fang, Linjun; Xu, Renjie (Frontiers in Neuroscience, 2025)
ObjectivesIn this study, we evaluated the key features of the 100 most-cited publications on optic nerve regeneration from 2005 to 2025 employing bibliometric and visual analysis.MethodsThe data for this study were obtained from a comprehensive search across multiple databases, including the Web of Science, Scopus, and Dimensions. We identified the top 100 most-cited articles published in each database from 2005 to 2025, merged and deduplicated the results, and selected the 100 most-cited papers on optic nerve regeneration. After extracting key details such as titles, authors, keywords, publication information, and institutional affiliations, a bibliometric analysis was conducted.ResultsThe top 100 most cited papers on optic nerve regeneration published between 2005 and 2025, accumulating 34,636 total citations with a median of 346 citations per paper. Prof. Zhigang He emerged as the most prolific author with 19 publications. The United States contributed 59 papers, while Harvard University led institutions with 30 publications. Key research themes included optic nerve regeneration, CNTF, gene therapy, and retinal ganglion cells.ConclusionOur analysis of top-cited optic nerve regeneration research reveals sustained United States leadership in output and innovation. Early work focused on neuronal signaling pathways (PTEN/mTOR, KLF family), while current studies explore novel targets and biomaterials. Global collaboration among the United States, China, and European nations has accelerated progress. Key challenges remain in achieving functional long-distance regeneration. Future direction should prioritize the development of multi-target therapeutic methods, precise drug delivery, and the control of inflammation to improve nerve regeneration efficiency.